Intento autolítico: incidencia de casos por grupos de edades (15-19 años) atendidos en el Hospital Provincial General Docente de Riobamba en el periodo comprendido entre enero 2017 – diciembre 2017 - Jorge Anthony, Sampedro Guerrero (2018)
Context: In Ecuador there are reports of individuals from the age group of 15 to 29 years old who died as a result of suicide. To determine the incidence of autolytic attempts by age groups (15-19 years) treated in the Provincial General Teaching Hospital of Riobamba in the period between January-December 2017. A non-experimental, descriptive study was carried out. retrospective and cross-sectional through the search of clinical histories with autolytic intent selected from an institutional database, later information of the study parameters was collected such as: sex, ethnicity, habitual residence, age, schooling, marital status, among others; the data was tabulated through the Excel 2010 program. 125 cases of autolytic attempt were obtained referring to the year 2017, having as a main factor the sentimental problems (39%) as the primary cause of this pathology, with a greater predisposition of the female sex (53%), single marital status (65%), age group between 15 to 19 years (37 individuals), habitual residence of the Riobamba canton (96 individuals) and the most used suicide method was the use of drugs (40%). The incidence rate of the age group most susceptible to the autolytic attempt (15-19 years) with a value of 26.31 per 1000 patients seen in the Hospital. That corrective measures should be taken in basic pathologies, such as: depression, physical and psychological violence, drug use and alcoholism, which triggers the autolytic attempt through awareness and prevention campaigns.